Advances in treating exposed fractures - Pedro Nogueira Giglio; Alexandre Fogaça Cristante; José Ricardo Pécora; Camilo Partezani Helito; Ana Lucia Lei Munhoz Lima; Jorge dos Santos Silva (Revista Brasileira de Ortopedia, 2015)
The management of exposed fractures has been discussed since ancient times and remains of great interest to present-day orthopedics and traumatology. These injuries are still a challenge. Infection and nonunion are feared complications. Aspects of the diagnosis, classification and initial management are discussed here. Early administration of antibiotics, surgical cleaning and meticulous debridement are essential. The systemic conditions of patients with multiple trauma and the local conditions of the limb affected need to be taken into consideration. Early skeletal stabilization is necessary. Definitive fixation should be considered when possible and provisional fixation methods should be used when necessary. Early closure should be the aim, and flaps can be used for this purpose.